Analysis Of English Curriculum In 11 Grade Of Udomsasn Wittya School Thailand - Sholihah, Khilayatus (Jetlal, 2017)
Curriculum is the device of subjects and educational programs provided by the organizers of an educational institution which contains lesson plans that will be given to participants of lessons over a period of education with certain goals. In this research, the researcher would like to analyze about the English curriculum in 11th grade of Udomsasn Wittya School Thailand. The formulation of the research problems were: 1. How is the curriculum of English Subject at Thailand school designed ? ,2. How is the learning course of English Curriculum in Thailand at 11th grade designed ?,3. How is the lesson plan of English Curriculum in Thailand at 11th grade designed ? Research Method: 1) the research design of this research was qualitative content analysis with descriptive qualitative approach. 2) the subject of this research was Thailand Basic Education Core Curriculum B.E. 2551 (A.D. 2008). 3) the data in this research were described and analyzed based on the research questions and the data sources were documents. 4) the technique to collecting the data was content analysis technique. The result of the research showed that Thailand curriculum framework, English syllabus, and the lesson plan were conducted with several common elements of general curriculum based on the theory. The Thailand Curriculum contains the educational environment needs and fulfiled with specific curriculum element and its function and purpose.